PENYULUHAN TENTANG TANDA-TANDA BAHAYA DALAM KEHAMILAN DI DESA PURBA TUA KECAMATAN PADANGSIDIMPUAN TENGGARA TAHUN 2020 - Maryam Latifah Harahap (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
Failure in the breastfeeding process is often caused by the emergence of several problems, both in terms of problems for the mother and the baby. For some mothers who do not understand this problem, breastfeeding failure is often considered a problem for children only. One of the factors that cause the lack of breastfeeding is less milk production. Many factors that cause the smoothness of breastfeeding are less, namely problems for mothers and babies. Problems in the mother are inverted nipples, mastitis or breast abscess, swollen breasts, and sore nipples. In infants, it is generally an error in lactation management, which causes a decrease in milk production (lack of milk syndrome). Papaya leaves contain alkaloids that are useful for nursing mothers in facilitating breast milk. Because the content can stimulate the production of breast milk. This activity aims to provide knowledge to Breastfeeding Mothers in Purba Tua Village, Southeast Padangsidimpuan District, about the benefits of papaya leaves as a breast milk launcher, provide understanding of mothers in breastfeeding and provide training on making instant sweet papaya leaf powder as an effort to facilitate breastfeeding. This community service activity plan uses counseling methods to socialize the benefits of papaya leaves, then training on making papaya leaf sweet instant powder, as well as an evaluation stage regarding processing efficiency of papaya leaf sweet instant powder and sedu drinks.